(untitled) (Japan, 1994)
The book presents an informational text together with comprehensive and easy to read statistical data allowing the reader to quickly grasp an insight into modern-day Japan. " NIPPON" has been published annually except in 1960 and 1991,...
Keywords: Japan; History